Skrinning Resep Interaksi Obat Pasien Diabetes Melitus Dan Hiperkolestrol Periode Oktober S.D Desember 2023 Di Rumah Sakit Advent Medan - Khairunnisa Lubis, Nazla (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Prescription screening is done to prevent the presence or absence of errors in drugs. Prescription screening is a stage in pharmaceutical services carried out by pharmacists who provide pharmaceutical services and pharmaceutical personnel can receive prescriptions from patients. This study aims to conduct prescription screening for drug interactions in patients with diabetes and hypercholesterolemia in the period October to December 2023. Patients with diabetes mellitus and hypercholesterolemia often receive combination therapy, which increases the risk of drug interactions. Lack of understanding of the potential for drug interactions can result in patient safety risks. Therefore, this study focuses on prescription screening to identify and analyze possible drug interactions